1997
DOI: 10.1183/09031936.97.10122749
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single-dose zileuton on bronchial hyperresponsiveness in asthmatic patients treated with inhaled corticosteroids

Abstract: E Ef ff fe ec ct ts s oof f s si in ng gl le e--d do os se e z zi il le eu ut to on n o on n b br ro on nc ch hi ia al l h hy yp pe er rr re es sp po on ns si iv ve en ne es ss s i in n a as st th hm ma at ti ic c p pa at ti ie en nt ts s t tr re ea at te ed d w wi it th h i in nh ha al le ed d c co or rt ti ic co os st te er ro oi id ds s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Bronchial hyperresponsiveness to methacholine was significantly reduced with the use of Cys-LT antagonists in certain studies, 50,51 even in patients on concurrent treatment with inhaled corticosteroids. 52 In contrast, montelukast exerted no significant effect on methacholine reactivity in a 12-week treatment of 110 adult asthmatic patients. 53 EIB was significantly attenuated by Cys-LT modifiers.…”
Section: Effects Of Cys-lts Blockade In Models Of Asthmamentioning
confidence: 91%
“…Bronchial hyperresponsiveness to methacholine was significantly reduced with the use of Cys-LT antagonists in certain studies, 50,51 even in patients on concurrent treatment with inhaled corticosteroids. 52 In contrast, montelukast exerted no significant effect on methacholine reactivity in a 12-week treatment of 110 adult asthmatic patients. 53 EIB was significantly attenuated by Cys-LT modifiers.…”
Section: Effects Of Cys-lts Blockade In Models Of Asthmamentioning
confidence: 91%
“…In the histamine challenge study [114] that included patients on ICS, no improvement in baseline lung function before challenge tests was found after zileuton administration. This could be due to the high mean FEV 1 of the group that was 111% of predicted.…”
Section: Bronchodilator Effect Of Zileutonmentioning
confidence: 85%
“…Challenges were repeated twice in random order separated by at least 5 days. Neither zileuton nor placebo changed baseline airway calibre prior to bronchoprovocation, but the active drug rendered significant protection both to histamine (PC20 increased from 0.99 to 5.64 mg/ml) and to distilled water (PD20 increased from 3.10 to 9.31 ml) [114].…”
Section: Challenge Testsmentioning
confidence: 99%
“…Few other studies have been reported which make the results of the study by DEKHUIJZEN et al [6] of particular interest. As would be anticipated from studies of the effect of antileukotriene drugs on exercise [31] and cold air [32] a marked effect on the indirect challenge of nebulized distilled water was observed.…”
Section: Nc Barnesmentioning
confidence: 87%
“…Due to this effect, the results of studies assessing BHR in relation to any new drug which affects the inflammatory cascade in asthma, are always keenly awaited. Reported in this issue of the European Respiratory Journal, is a study on the effects of the 5-lipoxygenase inhibitor zileuton on BHR [6]. How does this study relate to our current understanding of the role, if any, of leukotrienes, in the pathogenesis of airways inflammation and BHR?…”
Section: Nc Barnesmentioning
confidence: 99%